The Strategy for Preventing Delays in the Crew Change Process on the Fleet of PT. Satrya Maritim Indonesia - Markus Asta (PIP Makassar, 2026)
This study aims to explore the factors contributing to delays in crew change processes at PT Satrya Maritim Indonesia and propose strategic solutions to mitigate these delays. Using a qualitative approach, the research involves in-depth interviews, observations, and document analysis to identify both internal and external factors influencing the delays. Internal factors include limited standby crew, unstructured crew rotation planning, and administrative errors, while external factors involve delays in visa and work permit processing, sudden changes in immigration policies, and weather-related transportation disruptions. The consequences of these delays are significant, impacting the company financially through fines, operational disruptions, and a decrease in crew performance due to extended work periods. The study recommends implementing a structured timeline for crew change, enhancing the standby crew database, digitalizing crew management systems, and improving coordination between internal and external parties. By adopting these strategies, PT Satrya Maritim Indonesia can reduce delays, enhance operational efficiency, improve safety, and strengthen its competitiveness in the global maritime industry.